ANALISIS KEPUASAN GURU MI HIDAYATUN NAJAH PADA WORKSHOP DEEP LEARNING: KUALITAS PROGRAM DAN MATERI PELATIHAN - Rustya, Dian; Fauzi, M Fauzi (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
The Merdeka Curriculum is currently transforming with the deep learning approach. The deep learning approach has been proven effective in increasing students’ awareness of values through reflective, meaningful, and contextual learning experiences. Teacher professional development can be an essential means of implementing deep learning. MI Hidayatun Najah conducted a Deep Learning Workshop to enhance teacher's understanding and expertise in applying Deep Learning. Therefore, this study was conducted to determine participant satisfaction with the quality of the programme and training materials at the Deep Learning Workshop at MI Hidayatun Najah Tuban. This study used quantitative methods. The quality of the Deep Learning Workshop programme had a positive and significant effect on participant satisfaction with the training by 47.9%. This can also be seen in the t-value (4.730), which is greater than the t-table (1.665) or a significance value of 0.000 or less than 0.05. The training material has a relationship with the training participant satisfaction variable of 0.252 or 25.2%. This can also be seen from the t-value (2.489), which is greater than the t-table (1.665) or a significance value of 0.015 or less than 0.05. Based on the research results, it can be concluded that the quality of the programme and training material has a significant effect on teacher satisfaction at MI Hidayatun Najah in the Deep Learning Workshop.